Influence of the keynote e-book on the EFL skills of the A2 level students at Universidad Iberoamericana del Ecuador - Viveros Almeida, Martha Aracelly; López Villacrés, María Fernanda (SATHIRI, 2025)
In order to develop the EFL skills of students at Universidad Iberoamericana del Ecuador (UNIB.E), there was a necessity to change the EFL material for another that offered innovative ideas for the students and teachers to interact more and for them not to be limited to the traditional book methods that are mainly focused in the use of grammar. As a consequence, it was implemented the use of Keynote e-book that works with the Keynote online platform. The use of this e-book started to show meaningful changes in the students’ communication skills, which is the reason why it was feasible to carry out a study about the influence of the new method on the A2 level students EFL skills. Therefore, the objective of this research is to compare the academic performance of the students in different semesters and determine the influence of the use of the e-book on the EFL skills of the students of A2 level at UNIB.E. It is essential to apply methods according to the new era, since the traditional methods are not related to the today’s times. In Ecuador, students are encouraged to ask questions instead of expressing their opinions and producing by themselves and use English in real contexts, so this new method gave learners the opportunity to experience English in meaningful situations, however it only could be reached through the use of online tools to make students participate, interact, and practice better . Therefore, by means of the use of this e-book, students and teachers can create a new class environment that allows learners communicating and developing fluency. This quantitative applied the observation of the English lessons by using a classroom observation evaluation, the pre-post estimation model, comparative statistics about the evaluations and grades obtained by the students in five semesters as well.
Keywords: Keynote e-book; teacher; Students; EFL; skills